The Cardiac Electrophysiology Web Lab - Cooper, J; Scharm, M; Mirams, G (Cell Press, 2016)
Computational modelling of cardiac cellular electrophysiology has a long history, with many models now available for different species, cell types, and experimental preparations. This success brings with it a challenge: how do we assess and compare the underlying hypotheses and emergent behaviours, in order to choose a model as a suitable basis for a new study, or characterize how a particular model behaves in different scenarios? We have created an online resource for the characterization and comparison of electrophysiological cell models under a wide range of experimental scenarios. The details of the mathematical model (quantitative assumptions and hypotheses formulated as ordinary differential equations) are separated from the experimental protocol being simulated. Each model and protocol is then encoded in computer-readable formats. A simulation tool runs virtual experiments on models encoded in CellML, and a website – https://chaste.cs.ox.ac.uk/WebLab – provides a friendly interface, allowing users to store and compare results. The system currently contains a sample of 36 models and 23 protocols, including current-voltage curve generation, action potential properties under steady pacing at different rates, restitution properties, block of particular channels, and hypo-/hyper-kalaemia. This resource is publicly available, open source, and free; and we invite the community to use it and become involved in future developments. Those interested in comparing competing hypotheses using models can make a more informed decision; those developing new models can upload them for easy evaluation under the existing protocols, and even add their own protocols.